2015
DOI: 10.3892/mco.2015.589
|View full text |Cite
|
Sign up to set email alerts
|

Association between δ-aminolevulinate dehydratase G177C polymorphism and blood lead levels in brain tumor patients

Abstract: Abstract. As the δ-aminolevulinic acid dehydratase (ALAD) G177C polymorphism affects the toxicokinetics of lead in the body, and the corresponding exposure to lead may increase the risk of adult brain tumors, we hypothesize that there is a possible association of the ALAD G177C genotype and the risk of brain tumors in human. Therefore, the aim of the present study was to clarify the role of the ALAD enzyme gene polymorphism at position G177C in the pathogenesis of brain tumors and its correlation to lead expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have indicated that due to its high sensitivity to prooxidant situations, δ -ALAD can be a reliable universal biomarker of oxidative stress—various observations evidence a negative correlation between enzyme activity and level of oxidative stress [20, 26]. δ -ALAD inhibition due to thiol group oxidation leads to δ -ALA autoxidation, further δ -ALAD inhibition, additional O 2 ·- generation, and antioxidant system depletion [26, 46]. Excess δ -ALA in the brain disrupts γ -aminobutyric acid/glutamate system causing neurotoxicity and cell death [19, 46] while decreased heme biosynthesis is known to cause neuronal cell dysfunction, since heme is critical for neuronal cell growth, differentiation, and survival [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that due to its high sensitivity to prooxidant situations, δ -ALAD can be a reliable universal biomarker of oxidative stress—various observations evidence a negative correlation between enzyme activity and level of oxidative stress [20, 26]. δ -ALAD inhibition due to thiol group oxidation leads to δ -ALA autoxidation, further δ -ALAD inhibition, additional O 2 ·- generation, and antioxidant system depletion [26, 46]. Excess δ -ALA in the brain disrupts γ -aminobutyric acid/glutamate system causing neurotoxicity and cell death [19, 46] while decreased heme biosynthesis is known to cause neuronal cell dysfunction, since heme is critical for neuronal cell growth, differentiation, and survival [47].…”
Section: Discussionmentioning
confidence: 99%
“…δ -ALAD inhibition due to thiol group oxidation leads to δ -ALA autoxidation, further δ -ALAD inhibition, additional O 2 ·- generation, and antioxidant system depletion [26, 46]. Excess δ -ALA in the brain disrupts γ -aminobutyric acid/glutamate system causing neurotoxicity and cell death [19, 46] while decreased heme biosynthesis is known to cause neuronal cell dysfunction, since heme is critical for neuronal cell growth, differentiation, and survival [47]. Literature data show that Ni is especially prone to bind to amino acids like cysteine and histidine, small peptides like glutathione, and amine-containing compounds thus accelerating the rate of oxidative damage [28].…”
Section: Discussionmentioning
confidence: 99%
“…Functional consequences of rs1800435 SNP include the following: (i) increased risk for meningioma in carriers of the minor allele, which was not clearly related with serum lead levels or lead exposure , (ii) lack of modification of the risk for renal cell carcinoma among individuals with working exposure to lead, while other SNPs in the ALAD gene, such as rs8177796 and rs2761016 increased this risk , (iii) increase of lead placental levels in pregnant women related with the minor allele, which was more marked in homozygotes , (iv) modification of survival after onset of frontotemporal dementia or motor neuron disease caused by hexanucleotide repeat expansions in chromosome nine open reading frame (C9ORF72) , (v) influence in the toxic effect of lead on peripheral nerve of workers exposed to lead (lower motor and sensorial nerve conduction velocities in rs1800435CC homozygotes than in rs1800435G allele carriers at the same concentrations of lead in blood and urine , (vi) lack of modification of the effects of blood lead levels on cognitive function in adolescents and adults with environmental exposure to lead.…”
Section: Discussionmentioning
confidence: 99%